LISTENING SKILLS IN CHILDREN AGED 5-6 YEARS - Chrisma Arum Kartikadewi; Siti Wahyuningsih; Warananingtyas Palupi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research is to improve the ability to listenthrough the music and movement activity using traditional song. The type of this research is Kurt Lewin model class action research with qualitative data approach and quantitative data. The subjects of this study were children aged 5-6 years in Aulia Surakarta kindergarten in the academic year 2017/2018. Qualitative data validity using source triangulation and method triangulation. Meanwhile, quantitative data validity using construct validation. Data analysis technique using comparation descriptive and interactive model. Result of this research of class activity showed that through music activity and movement using traditional song , the students paid attention to movement and song for 10-15 minutes, the students can repeat the movement when the song is playing again and the students can do the simple verbal instruction from the teacher so that from music activity and movement using traditional song can improve the pay attention ability to the students of children aged 5-6 years in Aulia Surakarta kindergarten in the academic year 2017/2018.